2021
DOI: 10.1007/978-3-030-69221-6_146
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Efeects of Entrepreneurial Education Towards Antecedents of Entrepreneurial Intention Among Undergraduate Students

Abstract: The dramatic rose numbers of graduated students from higher education institutions cause unemployment issues among youth in Malaysia. Therefore, the entrepreneur indicated as one of the overcome determinants to against this issue. This study intended to identify the factors that influence entrepreneurial intention among undergraduate students among University Malaysia Kelantan since University Malaysia Kelantan is an entrepreneurial university. A total of 370 undergraduate students selected randomly, and all r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The study findings indicate that ESE and EA have a significant and direct association with the EI. The study results confirms that the Chinese higher vocational college students who have a positive attitude to start and run their own companies have a positive EI, consistent with the studies by Said et al (2021) and Su et al (2021) . It also justifies that the students from Chinese higher vocational college who believe in their abilities to achieve the set targets in the critical conditions are more inclined to have higher EI as supported by the study from Fernandez-Perez et al (2019) .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The study findings indicate that ESE and EA have a significant and direct association with the EI. The study results confirms that the Chinese higher vocational college students who have a positive attitude to start and run their own companies have a positive EI, consistent with the studies by Said et al (2021) and Su et al (2021) . It also justifies that the students from Chinese higher vocational college who believe in their abilities to achieve the set targets in the critical conditions are more inclined to have higher EI as supported by the study from Fernandez-Perez et al (2019) .…”
Section: Discussionsupporting
confidence: 88%
“…For example, Acuna-Duran et al (2021) , Boubker et al (2021) , Su et al (2021) , and Tehseen and Haider (2021) have confirmed that a person’s attitude toward entrepreneurship is positively and significantly associated with their intention to start a business. Although, different research studies have been conducted in various cultural contexts and economies but most of these studies still show that there is a significantly positive effect of EA on EI (e.g., Utami, 2017 ; Pejic et al, 2018 ; Said et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation